Shakespeare, Cardenio, and the Vertue Manuscripts - Lupić, Ivan (2010)
This paper traces the history of George Vertue's extracts from the Accounts of the Treasurer of the Chamber, today part of MS. Rawl. A. in the Bodleian Library. The extracts, relating to performances of plays at the court of James I and made in 1749 when Rawlinson acquired the relevant manuscripts, reached William Oldys and, probably later, David Garrick. Through George Steevens, who obtained the extracts from Garrick and fortunately copied them entire into his annotated copy of Langbaine's 1691 Account of the English Dramatic Poets (British Library MSS Add. 22592-22595), the information which the extracts contained entered the eighteenth century Shakespeare variorum. The vague yet frequent references to the papers of Mr. Vertue caused a great deal of confusion among those who were not possessed of the extracts but who had to take into account the historical data occasionally quoted from them. The example of Cardenio, a play mentioned in the Chamber Accounts for 1612-13, serves as the lens through which the history of the way in which the Vertue extracts--a fascinating instance of manuscript culture surviving within the printed book--were used in the eighteenth century, and beyond.